2017
DOI: 10.1021/acs.jpca.7b03823
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Investigation of π–π Interactions in Near-Edge X-ray Fine Structure (NEXAFS) Spectroscopy of Paracyclophanes

Abstract: NEXAFS spectroscopy has potential for study of packing and order in organic materials but only if intermolecular effects are understood. This work studies how π-π interactions between adjacent unsaturated groups affect their NEXAFS spectra, with a broader goal of building a general understanding of the role of intermolecular effects in NEXAFS spectroscopy. These effects are examined using paracyclophane (PCP) molecules, in which the benzene-benzene separation distance is controlled by varying the length of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…A clear red shift is observed of all carbon 1s → π* transitions upon aggregation, consistent with the calculations of Ho et al This indicates that the energy and form of the π* transitions in P3HT are defined not only by ring planarity, but also by the ring–ring interactions between adjacent chains. In their recent study of paracyclophanes in which the phenyl/phenyl ring separation was rigorously controlled, Perera and Urquhart demonstrated that this “red shift” was due to π/π interactions between adjacent aromatic groups . These π/π interactions become more significant at distances smaller than the van der Waals separation for carbon (two times the van der Waals radius, or 3.4 Å), but this effect persists weakly at larger ring separations .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A clear red shift is observed of all carbon 1s → π* transitions upon aggregation, consistent with the calculations of Ho et al This indicates that the energy and form of the π* transitions in P3HT are defined not only by ring planarity, but also by the ring–ring interactions between adjacent chains. In their recent study of paracyclophanes in which the phenyl/phenyl ring separation was rigorously controlled, Perera and Urquhart demonstrated that this “red shift” was due to π/π interactions between adjacent aromatic groups . These π/π interactions become more significant at distances smaller than the van der Waals separation for carbon (two times the van der Waals radius, or 3.4 Å), but this effect persists weakly at larger ring separations .…”
Section: Resultsmentioning
confidence: 99%
“…In their recent study of paracyclophanes in which the phenyl/phenyl ring separation was rigorously controlled, Perera and Urquhart demonstrated that this "red shift" was due to π/π interactions between adjacent aromatic groups. 49 These π/π interactions become more significant at distances smaller than the van der Waals separation for carbon (two times the van der Waals radius, or 3.4 Å), but this effect persists weakly at larger ring separations. 49 Spectroscopic fits presented in Table 2 show a red shift of a ∼ 10 meV between peak (A') in RRa-P3HT and (A) in RR-P3HT, and a narrowing of peak (A) with annealing.…”
Section: Resultsmentioning
confidence: 99%
“…The large separation between core and valence energies facilitates the description of the excited system by approximately evaluating the outer electronic structure in the presence of a core-level excitation, even though new implementations are becoming available that include many-body correlation effects [43]. In this respect, the half-core-hole approximation [44,45] appears to be quite adequate for molecular and adsorbed systems [46], and was validated for a variety of carbon-based systems [47,48,49,50,51]. The dichroism in the NEXAFS spectra is well reproduced by the simulations allowing for a detailed identification of adsorption orientations [52] and molecular-orbital symmetry [53].…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Among the currently available methods, the transition-potential density functional theory (TP-DFT) with the half core-hole approximation 29,30 is widely used to interpret the XAS spectra of ground states. 31,32 Ehlert et al extended the TP-DFT method to core excitations from valence-excited states, 33 and implemented it in PSIXAS, 34 a plugin to the Psi4 code. TP-DFT is capable of simulating (TR-)XAS spectra of large molecules with reasonable accuracy, as long as the core-excited states can be described by a single electronic configuration.…”
Section: Introductionmentioning
confidence: 99%